THE EFFECT OF ANNEALING TEMPERATURE ON THE TENSILE STRENGTH OF POLYLACTIC ACID FILAMENT PRINTED BY 3D PRINTER - Wicaksono, Leo Hutri; Muhammad Ghazali Arrahim (Journal of Renewable Energy and Mechanics, 2024)
The development of the industrial world is getting faster from time to time. The manufacturing industry is one of the industries that is very developed, especially in the use of technology. Although there have been some studies on the tensile strength of PLA filaments however, it is not yet clear about the effect of annealing treatment on the tensile strength of PLA filaments from 3D printers. Therefore, this study was conducted to determine the effect of annealing temperature on the tensile strength of polylactic acid material printed by 3D printers. This research uses experimental methods with the following conditions: The filament used is polylactic acid (PLA), specimens are printed to ISO 527-2 standard and the annealing treatment temperature are 50⁰C and 70⁰C. From the results of testing and data analysis that has been carried out, it can be concluded that annealing treatment is quite influential on the tensile strength value of polylactic acid (PLA) materials. The greater the annealing temperature, the higher the tensile strength value. At 50⁰C annealing the average tensile strength value is 15.89 MPa, while at 70⁰C annealing the average tensile strength value is 16.66 MPa.